Inovasi Pengemasan Produk UMKM Dalam Meningkatkan Nilai Jual Di Pasar Digital - Dodi Solihudin; Willy Prihantono; Nazwa Putri Nindya; Nizar Fazari Hidayat (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The Micro, Small, and Medium Enterprises (MSMEs) in the Tarikolot Subdistrict play a significant role in the local economy, yet they often face challenges in marketing and accounting management. A lack of knowledge and skills in these two areas results in limited market reach and ineffective financial management, which ultimately hinders business growth. The main issues faced by MSME actors include a lack of understanding of effective marketing strategies and insufficient basic accounting knowledge necessary for managing business finances. This leads to difficulties in promoting products and an inability to prepare simple financial reports. This training program aims to offer practical solutions by providing training focused on digital promotion strategies and easy-to-apply basic accounting practices for MSME actors. The methods employed include workshops, hands-on simulations, and intensive mentoring. The objective of this program is to improve MSME actors' skills in marketing their products effectively and managing their business finances using basic accounting principles. As a result, they are expected to increase their competitiveness and business sustainability. This training is expected to enhance the participants’ abilities to develop more structured marketing strategies and to understand and apply fundamental accounting in their daily operations. The outcomes will be measured by increased sales and improved financial reports of the participants. environments.